“Being There” in More-Than-Human Worlds: Place, Body, and Time in Ethnographic Research With Children - Hackett, Abigail; Myrstad, Anne (Journal of Childhood Studies, 2025)
In its attention to numerous small explorations with children and place, we reflect on how Edvard Munch’s painting “The Researchers” could almost be a scene from our ethnographic fieldwork with children. Prompted by our engagement with Munch’s painting, we explore three shifts in our own research practice over time. First, a shift from a sole focus on human relationships to the more-than-human nature of long-term research relations with place points to the bodily, relational nature of knowing that is not easily articulable in words. Second, we grapple with the shifting meaning and purpose of the “data set” within our research. By viewing data as part of a gift-giving logic, interconnection and shifting time scales are emphasized. Third, drawing on the Sámi concept of meahcci, we discuss how fieldwork became “unbounded” spatially and temporally, allowing new ways of knowing to emerge.